The effect of PGR red onion extract on the growth and yield of green mustard plants (Brassica juncea L.) - Ilmiah, Mufidatul; Anggarani, Mirwa Adiprahara (Jurnal Pijar Mipa, 2023)
Mustard plants are green plants that can be cultivated easily in various climatic conditions and can be consumed as a companion to cooking. In addition, mustard plants have enough content to meet the human body's needs. Giving a combination of PGR concentration of red onion extract and the right combination of media composition can affect mustard plants' growth and propagation system. This study aims to determine the effect of PGR red onion extract and the best composition of planting media, as well as to know whether there is an interaction between PGR and the composition of planting media regarding the growth and production of mustard plants. Sample selection is carried out using random sampling techniques in each population. The study was conducted in July-August 2023 in the Pasuruan City area using the 2-factor RAK (Group Random Design) research method. The first factor is the concentration of PGR, which consists of control (T0), concentration of 10% (T1), concentration of 20% (T2), and concentration of 30% (T3). The second factor is the composition of the planting medium with a ratio of soil, husk charcoal, and manure, namely (1: 2: 1) and (1: 1: 2). The results showed that the PGR factor of red onion extract with a concentration of 30% had a very real influence and gave the best results on the parameters of plant height, leaf width, and wet biomass of mustard plants. Planting media factors significantly affect and provide the best results in 1: 1: 2 treatment regarding plant height parameters at age 35-42 HST and wet biomass of mustard plants. The interaction between PGR and planting media has a real effect on the wet biomass of plants but does not have a real effect on plant height and leaf width of mustard plants.